Are public sector workers different? Cross-European evidence from elderly workers and retirees - Mirco Tonin; Michael Vlassopoulos (IZA Journal of Labor Economics, 2015)
We investigate whether public and private sector employees differ in terms of public service motivation using a representative sample of elderly workers from 12 European countries. We find that public sector workers, both those currently employed and those already retired, are significantly more prosocial; however, the difference in prosociality is explained by differences in the composition of the workforce across the two sectors, in terms of (former) workers' education and occupation. Subsample analysis reveals that public sector former workers in education are more prosocial even after controlling for a rich set of characteristics.
Keywords: D64; H83; J45; 330; Public sector; Public service motivation; Volunteering